Fisiologia de microalgas em vinhaça tratada e a temática dos resíduos na educação ambiental - Candido, Camila (Universidade Federal de São Carlos, 2019)
Vinasse is a highly polluting waste of the sugar-alcohol industry and generated in large quantities. Microalgae cultivation in vinasse is a way to use and treat the waste, save on the production of culture media and generate high value biomass. Several studies address this use, but there is a literature gap on investigations that improve the conditions to make its large-scale application viable. Studies are needed to select vinasse-tolerant strains, less costly residue treatments and algal biomass productivity determinations that consider the contaminant microorganisms inherent in waste cultures, such as fungi and bacteria. In this study two waste treatments, centrifugation and adsorption on smectite clay and activated charcoal were compared. Centrifugation was more economically and environmentally viable and, therefore, was adopted during this research. Ten microalgae strains were cultivated at different concentrations of the centrifuged vinasse and the most productive species were selected. As a means of increasing biomass production, the efficiencies of acclimation and artificial selection of microalgae were evaluated, but no positive results were obtianed. However, high microalgae productivities were obtained cultivating microalgae at predetermined concentrations of treated vinasse. Higher dry biomass, cell biovolumes, productivities and amount of total proteins were obtained in comparison with controls in BG11. In addition, these biomass produced in vinasse had a low proportion of contaminants, up to 22%. Haematococcus pluvialis, Scenedesmus quadricauda and Tetraselmis gracilis stood out for their high productivity. All strains evaluated had myxotrophic metabolism, but with different proportions regarding the use of inorganic and organic carbon. Evaluating conceptions of elementary students in relation to the theme of waste, it was observed that issues involving effluents, environmental legislation, regulatory agencies and mitigating measures are little known, which may explain the lack of action and recognition of environmental research by the society. We proposed a short course addressing different aspects of the theme, which proved to be important for changing behaviors towards the environment, and may contribute to the occurrence of future environmental preservation actions. Either by the selection of promising conditions for algal cultivation in vinasse or by the environmental education approach having waste as theme, this doctoral thesis is a contribution to a more sustainable and clean ethanol production.
Microalgae physiology in treated vinasse and the theme of waste in environmental education
Keywords: Resíduo sucroalcooleiro; Produção de biomassa; Fisiologia microalgal; Concepções ambientais; Educação ambiental; Sugar-alcohol residue; Biomass production; Microalgal physiology; Environmental conceptions; Environmental education; CIENCIAS BIOLOGICAS